Analysis Of Shortest Path Determination By Utilizing Breadth First Search Algorithm - Sihotang, Jonhariono; Simamora, Siska (SEAN Institute, 2020)
The rapid development of science requires the public to keep up with the development of such technology. The use of computers as one of the tools used to facilitate work and improve the efficiency and effectiveness of work is also high, this we can see from the development of such technology. Artificial Intelligence (AI) is one part of computer science that learns about how to make computers can do the job as humans do. At the beginning of its creation, the computer was only functioned as a counting tool. But along with the development of the times, the role of computers increasingly dominates the life of mankind. Computers are no longer only used as a calculation tool, more than that, computers are expected to be empowered to do everything that can be done by humans. People can be good at solving all problems in this world because people have knowledge andexperience. Knowledge is gained from learning. The more knowledge possessed by a person is certainly expected to be more able to solve problems. But the provision of knowledge alone is not enough, people are also given the sense to reason, draw conclusions based on their knowledge andexperience.